A simulation based digital twin approach to assessing the organization of response to emergency calls - Yann Penverne; Clea Martinez; Nicolas Cellier; Canan Pehlivan; Joel Jenvrin; Dominique Savary; Valerie Debierre; Florence Deciron; Anis Bichri; Quentin Lebastard; Emmanuel Montassier; Brice Leclere; et al. (npj Digital Medicine)
Abstract In emergency situations, timely contact with emergency medical communication centers (EMCCs) is critical for patient outcomes. Increasing call volumes and economic constraints are challenging many countries, necessitating organizational changes in EMCCs. This study uses a simulation-based digital twin approach, creating a virtual model of EMCC operations to assess the impact of different organizational scenarios on accessibility. Specifically, we explore two decompartmentalized scenarios where traditionally isolated call centers are reorganized to enable more flexible call distribution. The primary measure of accessibility was service quality within 30 s of call reception. Our results show that decompartmentalization improves service quality by 17% to 21%. This study demonstrates that reducing regional isolation in EMCCs can enhance performance and accessibility with a simulation-based digital twin approach providing a clear and objective method to quantify the benefits.”